Peran Unit Kegiatan Rohani Islam (ROHIS) dalam Membentuk Perilaku Sosial Siswa di SMA Negeri 1 Rantau Pulung - Awaludin, Rizal; Ifendi, Mahfudz; Prima, Anggra (Yayasan Miftahul Ulum Sangatta Kutai Timur (KEP. MENKUMHAM RI No. AHU-0014779.AH.01.04.Tahun 2018) bekerjasama dengan Jurusan Tarbiyah STAI SANGATTA Kab. Kutai Timur., 2025)
This study aims to describe the role of the Islamic Spiritual Activity Unit (ROHIS) in shaping the social behaviour of students at SMA Negeri 1 Rantau Pulung, as well as identifying the supporting and inhibiting factors. The research method used is descriptive qualitative, with data collection through observation, interviews, and documentation. The results of the study indicate that ROHIS plays a role in: (1) shaping religious character through routine activities such as Wednesday Prayer, which is held every week on Wednesdays with congregational dhuha prayers followed by collective prayers and halal bi halal, and Friday Taqwa, which is held at the beginning of each month on the first week with a religious lecture delivered by students of SMA Negeri 1 Rantau Pulung and collective prayers; (2) fostering good moral character through PHBI activities and the promotion of the 5S principles; (3) motivating students to study; (4) improving PAI learning outcomes; and (5) channeling students' interests and talents in Islamic arts, where students are free to express their interests and talents within ROHIS, such as habsyi. Supporting factors include school support, active student participation, and the availability of facilities and infrastructure. Hindering factors include a lack of student interest, insufficient socialisation, negative stigma, and peer influence. This study concludes that ROHIS plays a significant role in shaping students' social behaviour through various structured and planned activities. However, further efforts are needed to overcome the inhibiting factors so that the role of ROHIS can be more optimal.